The Effect of Stroke Up with Ignition Timing Variations on The Programmable CDIon The Engine Performance of The Gl Pro Neotech Motorcycle in 1997 - Iqbal Aditya Nugraha; Dwi Widjanarko (Universitas Negeri Semarang, 2026)
Stroke-up modification and ignition timing adjustment are commonly used to improve motorcycle engine performance, yet their combined effect requires controlled empirical verification. This study examined the effect of a stroke-up crankshaft combined with programmable CDI ignition timing variations on compression pressure, torque, and power output of a GL Pro Neotech 160 cc motorcycle. Methods: A quantitative true-experimental method was applied through engine performance testing under controlled workshop conditions. The standard crankshaft was compared with a stroke-up crankshaft, while ignition timing was adjusted to 15°, 16°, and 17° before top dead center using a programmable CDI. Primary data were obtained from compression tests and chassis dynamometer measurements across 5000–10000 rpm, then analyzed descriptively using average values, tables, and performance graphs. Results: The stroke-up modification increased compression pressure from 12.43 bar to 15.67 bar, equivalent to a 26.1% increase. The 15° timing produced strong low-to-medium speed torque, while the 16° stroke-up configuration showed the most stable and superior performance at medium-to-high engine speeds, reaching 16.71 Nm at 6000 rpm and peak power around 7000 rpm. Conclusion: Stroke-up modification combined with 16° ignition timing is the most effective configuration for improving motorcycle engine performance under the tested operating conditions and rpm range.